Teologi Guanxi: Sebuah Upaya Memahami Aspek Teologi Relasional dalam Budaya Tionghoa - Baito, Linus (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2019)
AbstractThis article aims at constructing a theology of business starting from the Chinese principle of relationship which is known as guanxi. Many have seen the role of guanxi in the process of China’s economic growth. Guanxi plays a philosophical role not only in economic life, but also in social as well as cultural ones. Using Robert Schreiter’s method of intercultural theology, this study finds that the philosophical concept of guanxi offers values compatible with a Christian theology of relationship. Interacting the two resources would provide a strong basis for constructing a theology of business. AbstrakArtikel ini bertujuan membangun sebuah teologi bisnis yang bertitik tolak dari prinsip Tionghoa yang dikenal sebagai guanxi. Banyak orang telah menyadari peran guanxi dalam proses pertumbuhan ekonomi Tiongkok. Guanxi memainkan peran filosofis bukan hanya dalam kehidupan ekonomi, tetapi juga sosial dan kultural. Menggunakan metode teologi interkultural dari Robert Schreiter, studi ini menemukan bahwa konsep filosofis guanxi menawarkan nilai-nilai yang kompatibel dengan teologi relational Kristen.